Exchange rate risk and economic reform: the case of endogenous institutional change in China - Wolfgang Veit (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2005)
Over the past 15 years the mutual importance of institutional economics and development economics have grown strongly. This paper attempts to apply institutional analysis to issues of economic development by analysing China?s reform process after her accession to the WTO on the background of the hypothesis of vertically dependent institutions. It will be shown that institutions on a lower level (e.g. a fixed exchange rate regime) are dominated by higher level institutions like (e.g. laws governing firms, financial and labour markets). The latter are dominated by institutions on a higher level, for example by regulations governing the economic and political system. Consequently, economic policy options like a change in the exchange rate regime will depend on adjustments in areas ranging from constitutional to company law. In the second chapter, the concept of hierarchical institutions is introduced. In the third chapter, the general results of China?s recent trade liberalisation under WTO rules and the issue of a fixed exchange rate to the US Dollar are recounted. In the fourth chapter, reforms necessitated by China?s accession to the WTO, and reflected by the present exchange rate regime, are identified. This is followed by the analysis of institutions that are conducive to successful implementation of those reforms in China.
Keywords: 330